The financial consequences of undiagnosed memory disorders - Carole Roan Gresenz; Jean M. Mitchell; Belicia Rodriguez; R. Scott Turner; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2024)
We examine the effect of undiagnosed memory disorders on credit outcomes using nationally representative credit reporting data merged with Medicare data. Years prior to eventual diagnosis, average credit scores begin to weaken and payment delinquency begins to increase, overall and for mortgage and credit card accounts specifically. Credit outcomes consistently deteriorate over the quarters leading up to diagnosis. The harmful financial effects of undiagnosed memory disorders exacerbate the already substantial financial pressure households face upon diagnosis of a memory disorder. Our findings substantiate the possible utility of credit reporting data for facilitating early identification of those at risk for memory disorders.
Keywords: I1; G41; G51; 330; debt repayment; memory disorders; credit cards; mortgages